2010
DOI: 10.4103/0189-6725.62843
|View full text |Cite
|
Sign up to set email alerts
|

Is nonoperative management of adhesive intestinal obstruction applicable to children in a resource-poor country?

Abstract: Nonoperative management was unsuccessful in this setting. Open adhesiolysis may be adopted in children to prevent avoidable morbidities and mortalities in settings with limited resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 10 publications
2
20
1
2
Order By: Relevance
“…[10] Al-Salem et al also reported that 40 (91%) of 44 children required laparotomy in their series. [13] In both publications, the authors advocated surgical adhesiolysis in children with ASBO.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[10] Al-Salem et al also reported that 40 (91%) of 44 children required laparotomy in their series. [13] In both publications, the authors advocated surgical adhesiolysis in children with ASBO.…”
Section: Discussionmentioning
confidence: 91%
“…[10,13] Such assertions have been refuted with the reporting of successful non-operative management. However, the optimal management of ASBO in the pediatric population is continuously debated in literature and served as an impetus for the current study.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Остальным необходимо проводить динамическое рентгенокон-трастное исследование -пассаж бария по кишечнику [10,15,21]. Малоинформативность обзорной рентгено-графии, особенно на ранней стадии заболевания, обу-словлена тем, что нет еще четкого перераспределения жидкости и газов в кишечнике, дающего классические рентгенологические признаки (арки и чаши Клойбера) [10,28,29].…”
Section: неинвазивные методы диагностикиunclassified
“…Послеоперационный период характеризуется не только меньшим болевым синдромом, быстро восста-навливающейся перистальтикой кишечника и активно-стью ребенка, но и отсутствием осложнений со стороны послеоперационных ран, хорошими косметическими результатами, сокращением сроков госпитализации, а следовательно, улучшением качества жизни пациен-тов [29,41].…”
Section: эндоскопическая диагностикаunclassified